Do subordinated debt holders discipline bank risk-taking? Evidence from risk management decisions - Belkhir, Mohamed (Journal of Financial Stability, 2013)
I test the market discipline of bank risk hypothesis by examining whether banks choose risk management policies that account for the risk preferences of subordinated debt holders. Using around 500,000 quarterly observations on the population of U.S. insured commercial banks over the 1995–2009 period, I document that the ratio of subordinated debt affects bank risk management decisions consistent with the market discipline hypothesis only when subordinated debt is held by the parent holding company. In particular, the subordinated debt ratio increases the likelihood and the extent of interest rate derivatives use for risk management purposes at bank holding company (BHC)-affiliated banks, where subordinated debt holders have a better access to information needed for monitoring and control rights provided by equity ownership. At non-affiliated banks, a higher subordinated debt ratio leads to risk management decisions consistent with moral hazard behavior. The analysis also shows that the too-big-to-fail protection prevents market discipline even at BHC-affiliated banks.